2022
DOI: 10.1186/s13071-022-05430-4
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of the Malaria Box for Babesia microti in mice identifies novel active scaffolds against piroplasmosis

Abstract: Background An innovative approach has been introduced for identifying and developing novel potent and safe anti-Babesia and anti-Theileria agents for the control of animal piroplasmosis. In the present study, we evaluated the inhibitory effects of Malaria Box (MBox) compounds (n = 8) against the growth of Babesia microti in mice and conducted bioinformatics analysis between the selected hits and the currently used antibabesial drugs, with far-reaching implications for potent combinations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In conclusion, additional studies to identify safe and efficacious anti-theilerial drugs for use in horses are urgently needed. Large-scale compound library screening experiments have enabled the identification of potentially efficacious drugs in some apicomplexan systems, and similar studies are needed for T. haneyi [ 35 , 36 , 37 , 38 , 39 , 40 ]. Furthermore, while several compounds have demonstrated in vitro efficacy against T. equi , very few have been tested against T. haneyi , or against either parasite in vivo [ 5 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, additional studies to identify safe and efficacious anti-theilerial drugs for use in horses are urgently needed. Large-scale compound library screening experiments have enabled the identification of potentially efficacious drugs in some apicomplexan systems, and similar studies are needed for T. haneyi [ 35 , 36 , 37 , 38 , 39 , 40 ]. Furthermore, while several compounds have demonstrated in vitro efficacy against T. equi , very few have been tested against T. haneyi , or against either parasite in vivo [ 5 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common hematological complications of malaria and babesiosis are thrombocytopenia and anemia. Anemia is caused by a various of pathophysiologic mechanisms, including accelerated RBCs removal by the spleen, obligatory RBCs destruction at parasite schizogony, and ineffective erythropoiesis (Nie et al, 2021;Rizk et al, 2021;Rizk et al, 2022). Recent advancements have shown that a variety of cytokine dysregulations are indeed vital participants in inducing and accelerating the pathogenesis of hemolysis in malaria and babesiosis.…”
Section: Discussionmentioning
confidence: 99%
“…The mode of action for the antibabesial efficacy of MMV396693 is still unknown. However, our previous study (Rizk et al, 2022) suggested that both MMV396693 and ID might have a similar mode of action for inhibition Babesia parasite. The effectiveness of such compounds in combination therapy with other medication candidates can therefore be tested.…”
Section: Introductionmentioning
confidence: 92%
“…In this regard, several compounds recently demonstrated anti-piroplasm effects both in vitro and in vivo. For instance, the Malaria Box was used to screen for new potent antipiroplasm medications, such as 3-[(2-Hydroxyethyl)amino]-5-methylphenazin-5-ium "MMV396693," by testing it against the growth of several bovine Babesia and equine piroplasms in vitro and the B. microti parasite in vivo (Rizk et al, 2019;Rizk et al, 2022). The mode of action for the antibabesial efficacy of MMV396693 is still unknown.…”
Section: Introductionmentioning
confidence: 99%